The Empirical Importance of Precautionary Saving - Gourinchas, Pierre-Olivier; Parker, Jonathan A (American Economic Review, 2001)
One of the basic motives for saving is the accumulation of wealth to insure future welfare. Both introspection and extant research on consumption insurance find that people face substantial risks that they do not fairly pool. In theory, the consumption and wealth accumulation of price-taking households in an economy with incomplete markets differs substantially from the behavior of these same households in the equivalent economy with complete-markets. The question we address in this article is whether we find this difference to be large in practice. What is the empirical importance of precautionary saving? We provide a simple decomposition that characterizes the importance of precautionary saving in the U.S. economy. We use this decomposition as an organizing framework to present four main findings: (a) the concavity of the consumption policy rule, (b) the importance of precautionary saving for life-cycle saving and wealth accumulation, (c) the contribution of changes in risk to fluctuations in aggregate consumption and (d) the significant impact of incomplete markets on aggregate fluctuations in calibrated general equilibrium models. We conclude with directions for future research.